# Factorise(i) 6ab - b2 + 12ac - 2bc(ii) x2 + y - xy - x(iii) x3 - 2x2y + 3xy2 - 6y3(iv) a(a + b - c) – bc

(i) 6ab - b2 + 12ac - 2bc
= (6ab - b2) + (12ac - 2bc)
= b(6a - b) + 2c(6a - b)
= (6a - b) (b + 2c)
(ii) x2 + y - xy - x
= x2 - xy - x + y
= x(x - y) - (x - y)
= (x - y) (x - 1)
(iii) x3 - 2x2y + 3xy2 - 6y3
= (x3 - 2x2y) + (3xy2 - 6y3)
= x2(x - 2y) + 3y2(x - 2y)
= (x - 2y) (x2 + 3y2)
(iv) a(a + b - c) - bc
= a2 + ab - ac - bc
= a(a + b) - c(a + b)
= (a + b) (a - c)

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Polynomials - Zero to Hero42 mins
Genius Quiz | Polynomials40 mins
Zeros and Degrees of a Polynomial41 mins
Champ Quiz | Polynomials29 mins
Genius Quiz | Division of Algebraic Expressions37 mins
Introduction to Polynomials37 mins
Quiz | Imp. Qs. on Algebraic Identities65 mins
Basic understanding of Polynomials37 mins
Methods to find zeroes of a Polynomial-246 mins
Remainder Theorem and Factor Theorem38 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses